Theory and Optimization Study of Inertance Tube of 80 K Pulse Tube Refrigerator - Liu Shaoshuai; Zhang Hua; Zhang Ankuo; Chen Xi; Wu Yinong (Zhileng xuebao)
The pulse tube refrigerator working at liquid nitrogen temperature is widely used in many fields, such as high temperature superconducting. Based on thermoacoustic theory, the phase shift ability of the inertance tube with/ without reservoir is investigated using DeltaEC. A pulse tube refrigerator model is built to investigate the effect of different inertance tube on cooling performance. The simulation results show that the inertance tube without reservoir would has close phase shift ability to the single-segment inertance tube with a reservoir. The pulse tube refrigerator connecting with double-segment inertance tube and reservoir gives a better cooling performance, in which lowest temperature would reach 48.8 K. At last, the test system is built to verify the simulation results.